Effects of Moringa oleifera Leaf Extract on the Liver of Experimentally-Induced Diabetic Wistar Rats - Ikhsan, Wahyu; Suryono, Suryono; Purwandhono, Azham (Folia Medica Indonesiana, 2023)
Highlights: • This study examined the antioxidant flavonoid compounds derived from naturally sourced Moringa oleifera leaves. • 2. Moringa oleifera leaf extract was able to prevent tissue fibrosis and liver cirrhosis in diabetic rat models through the nonalcoholic fatty liver disease (NAFLD) pathway. Abstract: Diabetes mellitus is known as a risk factor for nonalcoholic fatty liver disease (NAFLD) which can progress to nonalcoholic steatohepatitis (NASH) and eventually lead to hepatocellular carcinoma (HCC) through various stages, including necro-inflammatory fibrosis, cirrhosis, and hepatitis. M. oleifera leaves contain flavonoid antioxidants, which inhibit reactive oxygen species (ROS) and oxidative stress in diabetes mellitus. This study aimed to investigate the potential of M. oleifera leaf extract at a dosage of 1,000 mg/kgbw to inhibit liver tissue fibrosis in diabetic rats. This study used a true experimental method with a post-test-only control group design. This study was conducted at the Faculty of Medicine, Universitas Jember, Jember, Indonesia, from November 2021 to January 2022 on 27 male Wistar rats that were divided into three groups of nine rats. The rats were induced with streptozotocin and M. oleifera leaf extract at a dosage of 1,000 mg/kgbw. Masson's trichrome staining and the Meta-analysis of Histological Data in Viral Hepatitis (METAVIR) scoring system were used to measure liver tissue fibrosis. Data were analyzed using the Kruskal-Wallis and Mann-Whitney tests to examine significant differences between groups. The results showed a significant difference in the degree of liver tissue fibrosis between the control and diabetes groups (p=0.00) as well as the diabetes and treatment groups (p=0.003). However, the results did not show any significant differences between the control and treatment groups (p=0.270). These findings suggested that administering M. oleifera leaf extract at a dosage of 1,000 mg/kgbw can inhibit liver tissue fibrosis. In conclusion, this study provides evidence that administering M. oleifera leaf extract can inhibit liver tissue fibrosis in diabetic rats.